Akhmet Baitursynov: Catalyst of Kazakh Linguistic Renaissance and Educational Reformer - Kalybayeva Zhadyra (World Scientific Reports, 2024)
Akhmet Baitursynov, a notable figure in Kazakh history, made significant contributions to the development of Kazakh language and education. His efforts were instrumental in reshaping Kazakh identity and literacy during the early 20th century. Ahmet Baitursynov was a central figure in the cultural and educational renaissance of the Kazakh people in the early 20th century. As an educator, linguist, and poet, his contributions were instrumental in the formation of modern Kazakh identity. This paper examines his educational methodologies, literary works, and his profound impact on the Kazakh language through the lens of his textbooks and pedagogical theories. Baitursynov’s philosophy centered on the use of the Kazakh language as the medium of instruction. He recognized the adverse effects of foreign linguistic influences and sought to purify and standardize Kazakh, creating textbooks and educational materials that were culturally relevant and accessible to Kazakh speakers​​. His seminal work "Oqu Quraly" (Teaching Tool) republished several times. Baitursynov developed a Kazakh alphabet based on Arabic, by excluding Arabic letters which is not used in Kazakh language, and added letters specific to the Kazakh language. This alphabet named Tote jazu which means straight writing. When he introduced shorthand, he proved that writing with it is physically convenient and that it does not tire the hand. A. Baitursynov contributed to the development of the Kazakh society, with his pedagogical innovations, and his enduring impact on Kazakh nationalism.